EVALUATION OF THE AD-HOC BODY IN THE ELECTION AND REGIONAL ELECTION IMPLEMENTATION PROCESS IN MALAKA REGENCY IN 2024 & ELECTION PROSPECTS FOR THE 2029 ELECTION - Syahrin B. Kamahi; Yohanes Fisher Keon; Yonathan H. L. Lopo (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This article evaluates the performance and institutional capacity of ad-hoc bodies in the implementation of the 2024 General Election and Regional Head Elections in Malaka Regency and analyzes their implications for strengthening electoral governance towards the 2029 General Election. Ad-hoc bodies—which include the District Election Committee (PPK), the Voting Committee (PPS), and the Voting Organizing Group (KPPS)—are temporary institutions that play a strategic role in ensuring the integrity of election stages at the local level. This community service-based research uses a descriptive qualitative approach through participatory observation, focus group discussions, and in-depth interviews with election organizers and stakeholders. The findings indicate that although the ad-hoc bodies are able to carry out administrative and technical functions in accordance with the regulatory framework, there are structural issues that affect the effectiveness and independence of the institutions, such as limited technical capacity, disproportionate workload, local socio-political pressures, and weak legal protection and welfare systems. These conditions have implications for the vulnerability of electoral governance at the grassroots level. This article emphasizes the need for a more sustainable, professional, and capacity-based reformulation of ad-hoc agency management policies as a strategy to improve the quality of local democracy ahead of the 2029 General Election.